Making the best of both worlds: Can high-resolution agricultural administrative data support the assessment of High Nature Value farmlands across Europe?. (January 2017) - Lomba, Angela; Strohbach, Michael; Jerrentrup, J. Sabrina; Dauber, Jens; Klimek, Sebastian; McCracken, David I.
Highlights: There is a need for methodologies to assess High Nature Value farmlands in the EU. The potential to use IACS data was tested in the German region of Lower Saxony. 3% of the UAA of Lower Saxony was estimated to support High Nature Value farmlands. The high spatial and temporal resolution makes IACS data suitable for HNVf assessment. Abstract: Worldwide, the role of farmlands for biodiversity conservation and the delivery of multiple ecosystem services has been widely acknowledged. In the European Union (EU), societal demands to include environmental conservation concerns within the Common Agricultural Policy (CAP) have resulted in the recognition of the importance of maintaining High Nature Value farmlands (HNVf). HNVf constitute complex social-ecological systems, which owe their nature conservation value to the maintenance of specific, mostly low-intensity farming systems, supporting high levels of species and habitats dependent on agricultural practices. Even though HNVf assessment in space and time is essential to evaluate the effectiveness of Rural Development Programmes, the diversity of rural landscapes across EU, the scarcity of data on farming systems, and the lack of common methodological guidelines has hampered the implementation of HNVf mapping and monitoring across Europe. Thus, there is a pressing need to develop and test methodological approaches that may support HNVf assessment across the EU. The Integrated Administration and Control System (IACS) which is mandatory for all EU Member States constitutes a system for the management and control of CAP payments to farmers. Essentially, IACS comprises high-resolution, spatially explicit information on the type and intensity of agricultural land-use. Even though such data exhibits high thematic, spatial and temporal resolution, IACS has seldom been used, due to significant access restrictions. Here, the potential to use IACS data to support the assessment of HNVf was evaluated within the German Federal State of Lower Saxony by implementing a recently developed methodological framework. Sets of indicators known to be essential for identifying potential HNVf and underlying farming systems (expressing landscape structure and composition, farming systems, and crop diversity), were derived from IACS. Spatial patterns of indicators were analyzed at two different scales to delineate the potential distribution of HNVf across Lower Saxony. Results highlighted that most regions in Lower Saxony were characterized by intensive farming practices including high livestock density, high share of intensive crops and low density of linear elements. Only 3% of the Utilized Agricultural Area (UAA) of Lower Saxony potentially constituted HNVf, with the majority of HNVf coinciding with mosaics of arable and/or permanent crops and semi-natural features under less intensive farming practices. Semi-natural grasslands, partially under agri-environment scheme management contracts, covered roughly 1% of the UAA and were mostly intermingled with other farmland habitats in extensively managed agricultural landscapes. In the context of the EU-wide HNVf assessment, IACS constitutes an important source of data, characterized by a high spatial, thematic and temporal resolution of data collected annually. Whilst having the potential for use in HNVf assessment, some challenges remain, especially due to significant access restrictions. Nevertheless, IACS constitutes a powerful tool to evaluate the extent and condition of HNVf across the EU countryside. Making use of IACS data in such a way could provide a stepping-stone towards achieving a more effective balance between the management and control of CAP support payments and the growing societal demands related to the maintenance and enhancement of farmland biodiversity and ecosystem services.